The two faces of user involvement: Everyday life and local context - Kristiansen, Tine Mechlenborg; Antoft, Rasmus; Primdahl, Jette; Petersen, Kim Hørslev (Tidsskrift for Forskning i Sygdom og Samfund, 2015)
In most developed countries, healthcare systems are increasingly faced with political demands to involve users in the planning and development of their services. This article reports findings from an ethnographic fieldwork that investigated an inter-organizational project involving user representation. The project was set up to develop an educational programme for people with rheumatoid arthritis (RA). By investigating user representatives’ experiences, our aim was to bring to light more general determinants and conditions of user involvement in health services. Drawing on an analytical framework within everyday life sociology, the analysis explored the dual concept of “conditions and conditionality”, metaphorically described in this article as “the two faces of user involvement”. From one perspective, everyday life experiences – living with RA, encounters with the health system and professional identities and work life – conditioned user representatives’ participation in the project. From another perspective, the local institutional context and interactions within the project framework conditioned the way in which users are involved. The ways in which these conditions changed over time are described, in relation to the specific spatial, temporal and social developments in both the everyday lives of the user representatives and in the local project.